Enhancing Speaking Proficiency through TikTok Duet Interactions among Eighth Grade at SMP Negeri 4 Padangsimpuan - Hutabarat, Mei Suhardo; Siregar, Rini Kesuma; Harahap, Nursaima (ETANIC Journal Of English Language Teaching And Applied Linguistics, 2024)
This research aims to explore an innovative approach to improve the language skills of eighth grade students using the duet feature of the TikTok application.This research applies a quantitative methodology to evaluate the effectiveness of using video conversations on TikTok in educational settings. The study involved 30 students from SMP Negeri 4 Padangsimpuan as the research sample. Data collection was conducted by providing students with a conversational text containing over 20 vocabulary items, followed by documenting their performance scores. These scores were then subjected to statistical analysis to evaluate the impact of the TikTok duet feature on the students' speaking ability. The results showed a significant fluctuation in the students' speaking ability, with an initial average pre-test score of 59.83 dropping to 34.16 in the first post-test. This decrease suggested a temporary decline in speaking skills. However, subsequent educational interventions, including debriefing and targeted speaking practice, resulted in significant improvement, as evidenced by an average score of 82.5 on the second post-test. Analysis revealed a significant increase of 37.89% in speaking ability from the pre-test to the second post-test, despite the initial decline.